#RESISTEIZIDORA: controvérsias do movimento de resistência das Ocupações da Izidora e apontamentos para a justiça urbana - Luciana Maciel Bizzotto (2015)
In this paper, considering the urban justice as a parameter, I present a critique of contemporary urban planning in Brazil. Urban justice is the struggle for recognition and equitable distribution of resources, giving greater emphasis to social mobilization than public policy the institutional path of urban planning. To advance this theoretical discussion, I develop a case study in the Region of Izidora, in order to map the controversy surrounding the urban occupation (squatters in Brazil) resistance movement settled there and its supporters network: the #ResisteIzidoras network. The controversy is the part of science not yet stabilized, as a situation in which the actors disagree. This methodology is part of the Actor-Network Theory (ANT) developed, among others, by Bruno Latour, in an attempt to break with the modern thought regarding the relationship between nature and culture, bringing together human and non-human elements, whose acts leave traces throughout the report. Since the emergence of the Izidoras Occupations in mid- 2013, a threat was launched of a forced eviction for the realization of the Enterprise Granja Werneck, as a result of the Urban Operation of Isidoro, approved in 2010. In the fight for housing rights, the #ResisteIzidoras network has emerged, laden with other meanings implicit in the idea of urban justice and inserted in an international network of social movements that gained ground in the current processes of resistance. How has the #ResisteIzidoras network prevented the forced eviction and contributed to a more just city so far? That is the question that, basing myself on the ANT, I intend to investigate. From the controversies inside this movement, I present, through interviews and news reports available on virtual media (newspapers, blogs and Facebook), the largest number of world views inserted in it. The purpose of this study is therefore to give the opportunity for as many players as possible express their wishes, which can be a way for academic research helps us to understand the different views that exist about our common world, and, than, point at other urban planning options - or non-planning.